Unus pro omnibus, omnes pro uno: A novel, evidence-based, unifying theory for the pathogenesis of endometriosis. (June 2017) - Laganà, Antonio Simone; Vitale, Salvatore Giovanni; Salmeri, Francesca Maria; Triolo, Onofrio; Ban Frangež, Helena; Vrtačnik-Bokal, Eda; Stojanovska, Lily; Apostolopoulos, Vasso; Granese, Roberta; Sofo, Vincenza
Abstract: The theory of retrograde menstruation as aetiopathogenesis of endometriosis formulated by John Sampson in 1927 shows clear shortcomings: this does not explain why retrograde menstruation is a physiological process that affects 90% of women, while endometriosis occurs in only 10% of cases; it also does not explain the endometriotic foci distant from the pelvis, nor explains the cases of endometriosis in male patients. The immunological alterations of the peritoneal fluid explains the effects of disease, such as the inhibition of the physiological processes of cytolysis, but does not explain the cause. There is evidence to support the hypothesis that ectopic müllerian remnants of the endometrium, endocervix and endosalpinx are items from the genital ridge leaked during organogenesis. It is known that tissues derived from coelomatic epithelial and mesenchymal cells have the potential to metaplastically differentiate into epithelium and stroma. In addition, the phenotype of the ectopic endometrial cells is significantly different from those ectopic. There is scientific evidence that, during organogenesis, the genes of the Homeobox and Wingless family play a fundamental role in the differentiation of the ducts of Muller and development of the anatomical structure of the urogenital tract. We present here a hypothesis that deregulation of genes and the Wnt signaling pathway Wnt/β-catenin leads to aberrations and deregulation within the mesoderm, thus, may cause aberrant placement of stem cells. In addition, immune cells, adhesion molecules, extracellular matrix metalloproteinase and pro-inflammatory cytokines activate/alter peritoneal microenvironment, creating the conditions for differentiation, adhesion, proliferation and survival of ectopic endometrial cells.